Práticas de cuidado de familiares com crianças prematuras em uma UTIN : um estudo transcultural - Nascimento, Ana Celi Silva Torres (2019)
Premature birth and the need for hospitalization in a Neonatal Intensive Care Unit (NICU) are impactful experiences that generate feelings such as anguish and suffering, in addition to causing changes in family dynamics. This study aimed to understand the care practices of family members of premature infants admitted to a Neonatal Intensive Care Unit in the light of Leininger's Transcultural Theory. It is a qualitative, descriptive, and exploratory study. Participant observation and semi-structured interviews were conducted with sixteen (16) family members of newborns admitted to the NICU of a public maternity hospital during May and June 2019. The software called Interface de R pour Multidimensionnelles de Textes et Questionnaire® (IRAMUTEC®) and the Bardin Content Analysis technique. The research was approved by CEP / UEFS with CAAE: 06704919.6.0000.0053. From the data analysis, the results were presented in three scientific articles: Family care practices for preterm infants in the Neonatal Intensive Care Unit; Perception of prematurity by family members in the neonatal intensive care unit; and social networks to support families of premature infants who experience hospitalization, all with a cross-cultural focus. Even with the presence of other family members in the setting of the neonatal unit, the mother figure stands out as strength and care for the baby. The need for support from health professionals in preparing the family for shared care was highlighted. The relevance of the presence of God was also highlighted to experience the peculiarities of premature children, considering spirituality as one of the supports to experience prematurity, reinforcing how cultural aspects interfere in the process of coping with illness and hospitalization, as Leininger maintains. The importance of the presence of the extended family as a protective factor for coping and overcoming this situation emerged. Knowing the family structure, its needs and cultural influences, including its social support network, enables a more humane and effective care, where the family will be part of the planning and decision-making for prematurity to be taken care of broadly, respecting biological, social, and psychological factors, in addition to being considered an inseparable element of culturally congruent care, thus contributing to the full recovery of the premature.